2012
DOI: 10.1093/ejcts/ezs128
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of cell surface expression of endothelial adhesion molecules by ursolic acid prevents intimal hyperplasia of venous bypass grafts in rats

Abstract: Our results suggest that UA-mediated inhibition of endothelial VCAM-1 expression reduces the infiltration of venous bypass grafts by CD45-positive cells and inhibits intimal hyperplasia. Apoptosis induction in SMCs may be another method in which UA reduces intimal thickening. UA may constitute a surgery-supportive pharmacon that reduces intimal hyperplasia of vein grafts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…It is likely that dietary 23-OHUA may have additional, monocyte-independent benefits. Indeed UA has been reported to protect the endothelium against inflammatory activation and dysfunction 27, 28 . Thus, protecting the endothelium against metabolic stress-induced injury and dysfunction may contribute to 23-OHUA’s anti-obesogenic and atheroprotective properties.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that dietary 23-OHUA may have additional, monocyte-independent benefits. Indeed UA has been reported to protect the endothelium against inflammatory activation and dysfunction 27, 28 . Thus, protecting the endothelium against metabolic stress-induced injury and dysfunction may contribute to 23-OHUA’s anti-obesogenic and atheroprotective properties.…”
Section: Discussionmentioning
confidence: 99%
“…NO and platelet-activating factor (PAF)] are released. [1][2][3][4][5] These activities are intended to restore homeostasis in the body, which depends on the relevant repair processes in damaged tissues. Therefore, the reasons for the development of many chronic lesions, such as infective endocarditis (IE), diabetic foot ulcerations (DFU) or chronic wound infections (CWI), include both microbial infection and pathological changes within the host tissue, which disturb these physiological repair processes.…”
Section: Introductionmentioning
confidence: 99%
“…Zeller et al reported that UA, which pretreated for 30 min before TNF-α was added, reduced VCAM-1 expressions by Real-time PCR and Western blotting in dose-dependent manners (Zeller I et al, 2012). These results suggested that UA inhibits the CAMs expression at both the transcriptional and protein expression levels (Zeller I et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…UA, a pentacyclic triterpene compound, widely exists in natural plants, such as Rosmarinus officinalis and Ocimum basilicum, and they show several biological effects including anti-tumor (You et al, 2001), antimicrobial (Fontanay et al, 2008), and anti-inflammatory activities (Subbaramaiah et al, 2000). Zeller et al reported UA interfeses with TNF-α-mediated expression of adhesion molecules downstream NF-κB activation (Zeller et al, 2012). UA inhibited NF-κB, NF-AT, and AP-1 in lymphocytes (Checker et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation